PENGARUH KEMAHIRAN BERPROSES TERHADAP HASIL BELAJAR SISWA SMA MELALUI MODEL PEMBELAJARAN KOOPERATIF - Hindarto, Nathan; Anwar, Khoirul (Lembaran Ilmu Kependidikan, 2007)
The aim of this work is to know the influence of the processing ability towardstudent learning result through a cooperative learning model. The work is done througha class action research method. The processing ability is succeed if the average scoreobtained by student is more than 8.00 and at least 90% the student obtained a scoremore than 6.00. The result of the research showed that at the end of the action, theaverage score of the student was 8,15 and 37 students (~ 94,13%) obtained a scoremore than 6,00. The processing ability contributed 64,8% toward the learning result.The learning result improvement can be known through the regressionÃ¢â¬â¢s equation, ÃÂ¶ =0,678 + 0,824 X.Keywords: pembelajaran kooperatif, kemahiran berproses, hasil belajar